Conflitos na fronteira amazônica: conservação e disputas nas áreas protegidas do Amapá – Brasil - Roni Mayer Lomba; Jadson Luis Rebelo Porto (Confins)
The article is an analysis of the fragmentation of the territory of Amapá, from the creation of the legally protected areas. Hence, the objective was to analyze this process of spacial intervention, which, in many cases, became areas pervaded by socioenvironmental conflicts. It is questioned that, such protected areas have not represented a real space for preservation or conservation, with several foms of dispute and manifestation of territory use, which inpact on the environment, economy and society. By the line of the critical thought, theoretical interpretations on the theme were carried out, as well as the use of data, maps and qualitative interviews. The article is divided into three sections: the first one presents a theoretical analysis about the Brazilian environmental agenda in a global context; the second, the historical formation of the state of Amapá and the units of conservation in its territory; the third one, the management and conflicts in the protected areas of Amapá, followed by the final considerations that bring the reflections aproached in the text.